Impact Analysis of Intermediate Heat Carrier on Heat Transfer in Furnace. (10th March 2020) - Li, Cheng; Zhang, Wei-Jun; Yi, Zhi; Li, Na; Li, Kai
Abstract : Intermediate heat carriers have been applied in engineering as enhanced heat transfer elements, but their theoretical analysis still needs to be improved. Therefore, an intermediate heat carrier is added to establish the quaternary model of the furnace gas under nongray radiation characteristics. Based on this model, an analytical expression of heat flux on the surface of the billet is derived. General rule of the impact of intermediate heat carrier on the thermal efficiency in the furnace can be properly derived by analytical calculation from a theoretical point of view. The results show that the longer the length of the intermediate heat carrier located at the top of the furnace, the greater the heat exchange capacity on the surface of the billet. Meanwhile, when the intermediate heat carrier is located in the center of the furnace top, the billet gets higher heat flux; the closer to both sides, the lower the heat flux. In addition, the influence that the surface emissivity of the intermediate heat carrier has on the heat transfer of the billet surface is related to the values of ε g and α gw . Comparison with previous literature shows that adding intermediate heat carrier can improve the heat exchange capacity of billet.